2018
DOI: 10.1155/2018/4784762
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Fracture Grouting Mechanism and PFC Numerical Simulation in Loess

Abstract: According to the model test of fracture grouting in loess, the grout changes with the pressure variation, which can be divided into three stages, foundation, expansion and fracturing, and diffusion, and ultimately splits into "Y" shaped grout fractures. Using PFC 2D particle flow software simulates the slurry diffusion process on loess, and the results of the simulation display the same "Y" shaped slurry vein with the experiment, which has a certain reference value for fracture grouting in loess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…Researchers began to simulate the diffusion process of grouting cement grout from the perspective of micro-mechanics. Among them, Zhang et al (2018a, b, c), Liu et al (2019), Zheng et al . (2021), Yu et al (2021) and Li (2020) respectively used the particle flow DEM software PFC 2D/3D to explain the cement grout diffusion range and pressure law during grouting.…”
Section: The Research Status On Numerical Simulation Of Rock Groutingmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers began to simulate the diffusion process of grouting cement grout from the perspective of micro-mechanics. Among them, Zhang et al (2018a, b, c), Liu et al (2019), Zheng et al . (2021), Yu et al (2021) and Li (2020) respectively used the particle flow DEM software PFC 2D/3D to explain the cement grout diffusion range and pressure law during grouting.…”
Section: The Research Status On Numerical Simulation Of Rock Groutingmentioning
confidence: 99%
“…In contrast, micro fractures cannot be injected. Zhang et al (2018a, b, c) introduced the two-stage governing equation of fracture deformation and established a theoretical model of fracture grouting diffusion considering the coupling effect of cement grout and rock. They also indicated that the smaller the crack width, the more significant the effect of fluid–solid coupling on the grouting diffusion process, which is consistent with Zheng's results.…”
Section: The Research Status On Numerical Simulation Of Rock Groutingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some scholars have carried out research on seepage grouting and splitting grouting, overall, the theoretical research on grouting engineering lags far behind engineering practice. In particular, there is a lack of systematic experimentation and research in the field of filling soil grouting; therefore, experience is often needed in grouting design, construction, and the evaluation of grouting effects, presenting an urgent problem to be solved [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion form of grout in coal seam cracks is di cult to obtain through laboratory tests or eld measurements. The PFC particle ow simulation method has been applied in many studies conducted in China and abroad (Sun et al2010;Yuan et al2011;Geng et al2012;Zhang and Shao 2018;Lei and Latham 2016). This method can reveal the mechanical law and coupling mechanism of the grouting process from a microscopic perspective, re ect the relationship between the macroscopic performance of grouting and the microscopic characteristics of the coal body, and simulate the crack expansion under different grouting pressures.…”
Section: Introductionmentioning
confidence: 99%